Analisis Pelaksanaan Bimbingan dan Konseling di SMPN 18 Kota Jambi - Chandra, Mutiara Putri; Syukur, Yarmis; T, Taufik (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Guidance and Counseling (BK) is one of the important components in the education system that aims to help students develop their potential optimally, both in academic, personal, social, and career aspects. At the junior high school level, BK services play a strategic role in shaping character, overcoming the problems of adolescent development, and guiding students in planning their future education. Therefore, improving the quality of BK services in SMPN 18 Jambi City is an urgent need. Efforts that can be made include opening counseling services outside of class hours, increasing the number of BK teachers in accordance with ideal standards, ensuring BK teachers have an appropriate educational background, and increase student literacy regarding the role and function of BK services. Thus, BK services are expected to play an optimal role in supporting student development, both in terms of academic and non-academic. Based on the results of research and analysis that has been conducted regarding the implementation of guidance and counseling services (BK) at SMPN 18 Jambi City, it can be concluded that BK services in this school have a significant role in supporting student academic, personal, and career development. BK services help students overcome various problems, such as low learning motivation, interpersonal conflicts, and future planning, to continue their education to the next stage.